2014
DOI: 10.1371/journal.pone.0098152
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Treatment in a US Commercially Insured, HIV-1–Infected Population

Abstract: ObjectiveRecent treatment patterns and cost data associated with HIV in the United States are limited. This study assessed first-line persistence and healthcare costs of HIV-1 in patients by treatment line and CD4 cell count.Methods MarketScan Commercial Claims and Encounters Database (2007–2011) and Lab Database (2007–2010) were used to construct two HIV-1 cohorts: 1) newly treated HIV-1–infected patients with ≥6 months' continuous enrollment prior to first third-agent drug claim (Newly Treated Cohort) and 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Allowing hospitalization costs to be driven exclusively by CD4 counts for both STR and MTR results in an ICER of $37,438 per QALY. Considering a different source of inpatient and other costs [ 10 ] similarly increases the ICER to $35,521 per QALY. Finally, assuming, upon failing 6 th -line therapy, a successive sequence of further therapy lines with efficacy, safety and cost parameterization equal to that of the 6 th -line, results in a dominant scenario for STR as compared to gMTR: an increase of 0.49 discounted QALY, accompanied by $14,348 in discounted total cost savings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Allowing hospitalization costs to be driven exclusively by CD4 counts for both STR and MTR results in an ICER of $37,438 per QALY. Considering a different source of inpatient and other costs [ 10 ] similarly increases the ICER to $35,521 per QALY. Finally, assuming, upon failing 6 th -line therapy, a successive sequence of further therapy lines with efficacy, safety and cost parameterization equal to that of the 6 th -line, results in a dominant scenario for STR as compared to gMTR: an increase of 0.49 discounted QALY, accompanied by $14,348 in discounted total cost savings.…”
Section: Resultsmentioning
confidence: 99%
“…Higher pill burden is associated with both significantly lower adherence rates and worse virological suppression [ 58 ]. Poor control of HIV [ 59 ], greater pill burden [ 12 ] and lower adherence [ 4 ] are all associated with higher risk of hospitalization and higher inpatient costs and other non-ART costs that may account up-until 45% of total lifetime costs of current HIV Care [ 10 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also used published estimates of HIV-related healthcare costs, first- and second-line ART costs, the costs of antibody testing, genotype resistance testing, and counseling and diagnosis [ 23 , 26 , 49 51 ]. Our base case assumed that second-line drug costs for drug-resistant patients were 1.24 times higher than first-line drug costs for drug-sensitive individuals [ 53 ], and varied this multiplier from 1 to 5 in sensitivity analysis. Annual PrEP costs included ART medication, laboratory fees (i.e., HIV antibody test every 2–3 months, sexually transmitted infections test every 6 months), and professional fees for patient visits and consultations [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, although various modelling exercises have been conducted, the likely costs of second and third-line treatments are unclear, although one limited study in the US showed that ‘…second and third-line treatments were both significantly more expensive than first-line treatment, increasing costs by 24% and 41% respectively’ [ 11 ]. Furthermore, as HIV and AIDS treatments are set to extend in scope and lengthen in time, critical infrastructural and professional deficiencies are already apparent: The management of HIV increasingly requires a multidisciplinary testing approach involving haematology, chemistry, and tests associated with the management of non-communicable diseases; thus, added expertise is needed.…”
Section: Introductionmentioning
confidence: 99%